Seberapa penting menguasai keterampilan konseling bagi konselor - Nuriyah, Devi Shinta (Maliki Interdisciplinary Journal, 2024)
Counseling skills are interpersonal and technical traits that a counselor uses to better understand and listen to their clients. By using these skills, a counselor helps clients overcome the obstacles that prevent them from living a happy life. These skills help build relationships, build trust, and ensure that clients feel heard and understood. The method used is descriptive analysis.